Activation of natural halloysite nanotubes by introducing lanthanum oxycarbonate nanoparticles via co-calcination for outstanding phosphate removal. Issue 14 (30th January 2019) - Wei, Yanfu; Yuan, Peng; Liu, Dong; Losic, Dusan; Tan, Daoyong; Chen, Fanrong; Liu, Hongchang; Zhou, Junming; Du, Peixin; Song, Yaran
Abstract : Efficient phosphate capture achieved via activating halloysite nanotubes to create functional alumina nanoparticles by anchoring La-based nanoparticles to tube surfaces. Abstract : Halloysite nanotubes were activated via co-calcination of halloysite and the precursors of lanthanum oxycarbonate (LO), generating reactive alumina nanoparticles and uniformly anchoring LO nanoparticles to halloysite surfaces. The resulting LO–alumina combination exhibits record-high phosphate adsorption capacity as well as excellence in adsorption selectivity and sewage phosphate removal.